Water Quality Status in Doon Valley Forest - Kumar, Om; Mathur, H. N. (Indian Forester, 1989)
The studies on water quality status have been carried out on the perennial streams. Song, Suswa and Reh, selecting the eight representatives sites. Temperature, conductivity and pH of water samples analysed have been described in this paper.